Trauma and Trust: How War Exposure Shapes Social and Institutional Trust Among Refugees - Hall, Jonathan; Werner, Katharina (Frontiers in Psychology, 2022)
The brutal wars in Iraq, Syria and now Ukraine have caused a massive influx of refugees to Europe. Turkey alone has received more than 4.8 million refugees. An important precondition for their economic and social incorporation is trust: refugees need to trust the citizens as well as the state and the justice system to find their place in the host country. Yet refugees’ propensity to trust may be affected by cultural differences between their home and host countries, their personal conflict exposure and the experiences they had on the run. This study investigates how individual differences in exposure to armed conflict and institutional breakdown shape two types of trust among refugees: Generalized social trust and trust in the institutions of the settlement country. We survey a large and diverse sample of refugees from Syria and Iraq living in Turkish communities and deploy well-established measures of conflict exposure, posttraumatic stress and posttraumatic growth. We find that higher degrees of conflict exposure are positively related to social trust, and to trust in courts and the police. These positive findings are largely driven by refugees who had very personal and emotionally powerful experiences. The psychological mechanism of posttraumatic growth cannot explain these findings, however, suggesting positive experiences of cooperation in the midst of war and displacement are potentially a better explanation for this finding than positive psychological changes resulting from trauma. At the same time, conflict exposure is negatively related to trust in political institutions. Posttraumatic stress may be the mechanism behind this result. We discuss the implications of these findings for the integration of war refugees – a topic that is tragically of great relevance today.